THE EFFECT OF WORK ENVIRONMENT AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE AT THE FACULTY OF PUBLIC HEALTH, UNIVERSITAS MUHAMMADIYAH JAKARTA IN 2024 - Fayyaza Zakaria (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
Performance is the result of a person's overall work in a certain period of time. To provide a good opportunity for employees to achieve their career ambitions, employee performance must be evaluated. The purpose of this study is to find out how employee performance is affected by the work environment and experience. Employees of the Faculty of Public Health, University of Muhammadiyah Jakarta became the research population, and the research design was cross-sectional with data collection through questionnaires. With a sample of thirty employees, the sampling method used in this study is accidental sampling. The findings of the univariate analysis showed that half of the employees had excellent performance (50.0%), more than half of the employees stated that the work environment was excellent (53.3%), and almost half of the employees had excellent work experience (43.3%). Creating a more comfortable workplace and a more advanced work experience can improve employee performance.